A Tool for a Fast and Accurate Evaluation of the Energy Production of Bifacial Photovoltaic Modules - Vincenzo d’Alessandro; Santolo Daliento; Mahmoud Dhimish; Pierluigi Guerriero (Solar)
In this work, we propose a simulation tool designed for the analysis and optimization of bifacial photovoltaic (PV) modules, which are currently under the spotlight in the renewable energy scenario. The tool is conceived to support researchers and engineers by providing fast and accurate predictions of the PV module yield under various operating and environmental conditions. For a chosen geographical site, the impact of module orientation, tilt, albedo, sky conditions, ambient temperature, and so on can be effortlessly determined. In case of nonuniformity across the cells dictated by localized architectural shading, dirt, bird drops, and defects, a circuit-based cell-level approach can be activated to compute the module production. An extensive simulation campaign is performed by assuming that the panels are installed in Naples without loss of generality. Results are shown to give detailed insights into the performance of bifacial modules, thus providing unambiguous guidelines for their correct installation. Further analyses are conducted to demonstrate the tool capability to quantify the detrimental influence of a poorly-irradiated cell on the backside, as well as of cracked cells.